Analisis Yuridis Terhadap Perbuatan Melawan Hukum Kegiatan Pengangkutan Hasil Tambang Berdasarkan Peraturan Daerah Kalimantan Timur Nomor 10 Tahun 2012 - Dhea Shaberina Dila; Yulianingrum, Aullia Vivi; Sunariyo, Sunariyo (Consensus : Jurnal Ilmu Hukum, 2025)
This study discusses the legal analysis of unlawful acts in the transportation of mining products based on East Kalimantan Regional Regulation No. 10 of 2012 concerning the Management of Public Roads and Special Roads for the Transportation of Coal and Palm Oil. The research focuses on identifying elements of unlawful acts, the implementation of regulations by local governments, and criminal provisions imposed on corporations that violate mining transportation regulations. The research uses a normative legal method by examining legislation, legal literature, and field data as supporting evidence. The results of the study show that violations of the obligation to build special roads, the use of public roads without permission, and non-compliance with technical provisions constitute unlawful acts both formally and materially. The implementation of local regulations faces challenges such as weak supervision and compensation practices that are not in accordance with the law, but it still provides a strong normative basis for local governments through administrative and criminal sanctions. The criminal provisions in the local regulation play a significant role as an instrument of deterrence against corporations, while also supporting the application of the principle of good mining practice and the protection of public safety and interests. Thus, this study emphasizes the importance of local law enforcement in maintaining order, public safety, and the sustainability of mining governance in East Kalimantan.